Islam Berkemadjoean Perspektif Globalisasi: Kontribusi Islam Indonesia pada Peradaban Global - Teguh Luhuringbudi; Fitri Liza; Novian Akbar (Mawaizh : Jurnal Dakwah dan Pengembangan Sosial Kemanusiaan, 2020)
This research is aimed at studying the role of the Muhammadiyah Association in global relationships based on slogan, watchwords, plans, and Islamic activities. This study uses a communication and media approach as an effort to discuss a Muhammadiyah organization in the era of globalization. The perspective used in this study is the perspective of "globalization" carried by Gill Branston and Roy Stafford with an analysis of the steps of cultural imperialism, free market and global analysis. This research proves that the higher the level of Muhammadiyah's active involvement and translation in socializing and contributing at the global level makes the position and role of this International Non-Government Organization proof and is obtained by many people.